Deregulation of initial teacher training. A neoliberal experience - Silva-Peña, Ilich; Peña-Sandoval, Cesar (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper addresses the problem of deregulation of initial teacher training under a neoliberal system. Chile was used as a social laboratory of political and economic transformation by a group of Chilean economists trained in the United States (Chicago Boys). The text provides historical background of the process carried out by the civil-military dictatorship in Chile, continued by the following governments. This political and historical framework makes it possible to visualize the Chilean university system, in which state institutions are affected by a self-financing model. We emphasize the analysis around the regulation/deregulation dichotomy as a public/private distinction. An example is the expansion of a private and deregulated offer of teacher training by regional state universities with low basal state contribution. Through these cases it is possible to observe that a model based on supply and demand advances in the destruction of the frontiers between public and private sectors. As a good laboratory, the example of Chile can be used to observe the effects of a neoliberal public policy.